GENERATION OF BIOGAS AND THERMAL ENERGY AT THE BOLO DAS OLIVEIRAS AGROINDUSTRY, POMBAL, PARAÍBA, BRAZIL (Nativa, 2024)
ABSTRACT: This study aimed to assess the potential for generation of thermal energy from biogas produced by a rural biodigester in the Bolo das Oliveiras Agroindustry, Pombal/PB, Brazil. The biodigester was fed every two days with 0.30 m3 of biomass (mixture of water and bovine manure), retention time of 45 days. Affluent and effluent samples were collected every 15 days for 75 days. The affluent had a higher (p < 0.05) solids contents than the effluent. The highest dissolved oxygen concentration (6.67 mg L−1) was observed in the affluent. The effluent had lower (p < 0.05) total alkalinity than the affluent at all sampling times. CH4 values were higher than CO2 values throughout the experiment. Biogas also contained trace proportions of H2S and NH3 (2/3 and 1/3 ppMV, respectively). CH4 emissions were estimated at 10.58 m3 day−1. CH4 was the major constituent of biogas, as indicated by flame combustion behavior. Generation of biogas and thermal energy at the Bolo das Oliveiras Agroindustry may be economically feasible, providing a minimum monthly savings of R$ 1,582.00.Keywords: biodigester; effluent; methane. Geração de biogás e energia térmica na agroindústria Bolo das Oliveiras, Pombal, Paraíba, Brasil RESUMO: Este estudo teve como objetivo avaliar o potencial de geração de energia térmica a partir do biogás produzido por um biodigestor rural na Agroindústria Bolo das Oliveiras, Pombal/PB, Brasil. O biodigestor foi alimentado a cada dois dias com 0,30 m3 de biomassa (mistura de água e esterco bovino), tempo de retenção hidráulica de 45 dias. Amostras de afluentes e efluentes foram coletadas a cada 15 dias durante 75 dias. O afluente apresentou teores de sólidos maiores (p < 0,05) do que o efluente. A maior concentração de oxigênio dissolvido (6,67 mg L−1) foi observada no afluente. O efluente apresentou alcalinidade total menor (p < 0,05) do que o afluente em todos os tempos de amostragem. Os valores de CH4 foram superiores aos valores de CO2 durante todo o experimento. O biogás também continha traços de H2S e NH3 (2/3 e 1/3 ppMV, respectivamente). As emissões de CH4 foram estimadas em 10,58 m3 dia−1. O CH4 foi o principal constituinte do biogás, conforme indicado pelo comportamento da combustão da chama. A geração de biogás e energia térmica na Agroindústria Bolo das Oliveiras pode ser economicamente viável, proporcionando uma economia mensal mínima de R$ 1.582,00.Palavras-chave: biodigestor; efluente; metano.